Mitigating antimicrobial resistance (AMR) using implementation research: a development funder's approach. Issue 2 (27th March 2023) - Khurana, Mark P; Essack, Sabiha; Zoubiane, Ghada; Sreenivasan, Nandini; Cordoba, Gloria Cristina; Westwood, Erica; Dalsgaard, Anders; Mdegela, Robinson H; Mpundu, Mirfin; Scotini, Rodrigo; Matondo, Augustine B; Mzula, Alexanda; et al.
Abstract: Despite the escalating burden of antimicrobial resistance (AMR), the global response has not sufficiently matched the scale and scope of the issue, especially in low- and middle-income countries (LMICs). While many countries have adopted national action plans to combat AMR, their implementation has lagged due to resource constraints, dysfunctional multisectoral coordination mechanisms and, importantly, an under-recognized lack of technical capacity to adapt evidence-based AMR mitigation interventions to local contexts. AMR interventions should be tailored, context-specific, cost-effective and sustainable. The implementation and subsequent scale-up of these interventions require multidisciplinary intervention-implementation research (IIR). IIR involves both quantitative and qualitative approaches, occurs across a three-phase continuum (proof of concept, proof of implementation and informing scale-up), and across four context domains (inner setting, outer setting, stakeholders and the implementation process). We describe the theoretical underpinnings of implementation research (IR), its various components, and how to construct different IR strategies to facilitate sustainable uptake of AMR interventions. Additionally, we provide real-world examples of AMR strategies and interventions to demonstrate these principles in practice. IR provides a practical framework to implement evidence-based and sustainable AMR mitigation interventions.